Analisis Fitokimia Ekstrak Daun Pepaya (Carica papaya L.) dengan Pelarut Etanol 70% - Meta Tri Yana (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Papaya leaves (Carica papaya L.) are a medicinal plant containing various secondary metabolites such as alkaloids, flavonoids, and saponins, which play a role in biological activities, including antibacterial and antioxidant properties. Phytochemical analysis is necessary to identify the active compounds extracted by specific solvents. 70% ethanol was chosen because it effectively dissolves both polar and semipolar compounds. Methods: This study used a qualitative method by extracting dried papaya leaves through maceration with 70% ethanol. The resulting extract was then phytochemically tested using specific reagents to identify compounds such as alkaloids (Mayer and Wagner), flavonoids (Mg-HCl test), tannins (FeCl?), saponins (foam test), and steroids and terpenoids (Liebermann–Burchard). Results: The test results showed that the 70% ethanol extract of papaya leaves contained alkaloids, flavonoids, saponins, tannins, and terpenoids, while steroids were not detected. Discussion: The phytochemical content found in papaya leaves contributes to their potential bioactivity, particularly as antibacterial and antioxidant agents. Ethanol 70% has been shown to be effective in extracting active compounds due to its semipolar nature. Conclusion: The ethanol extract of 70% papaya leaves contains various important phytochemical compounds that support its potential as a natural source for the development of herbal medicines and health products.